2001
DOI: 10.1055/s-2001-15821
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis Based on 18S rRNA Gene and matK Gene Sequences of Panax vietnamensis and Five Related Species

Abstract: Panax vietnamensis was discovered recently in Vietnam. Its bamboo-like rhizomes, called Vietnamese Ginseng, have attracted considerable attention because of their specific pharmacological activities. In order to define the taxonomic position of this new species and include it in the molecular authentication of Ginseng drugs, the 18S ribosomal RNA gene and matK gene sequences of P. vietnamensis were determined and compared with those of its related taxa, P. japonicus var. major and P. pseudo-ginseng subsp. hima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 0 publications
1
44
0
2
Order By: Relevance
“…We previously demonstrated that comparing sequences of the 18S ribosomal RNA gene and plastid matK gene was a powerful tool to authenticate herbal drugs. 10) The matK gene occurs as a 1.5 kb region embedded within a 2.6 kb intron of the transfer RNA gene for lysine (trnK).…”
mentioning
confidence: 99%
“…We previously demonstrated that comparing sequences of the 18S ribosomal RNA gene and plastid matK gene was a powerful tool to authenticate herbal drugs. 10) The matK gene occurs as a 1.5 kb region embedded within a 2.6 kb intron of the transfer RNA gene for lysine (trnK).…”
mentioning
confidence: 99%
“…Accordingly, not only interspecies but also intraspecies nucleotide substitutions were observed. Since Panax ginseng and Panax quinquefolius previously examined did not show such sequence variation within the same species, 8) the phenomena observed in Rheum species may be related to their self-incompatibility. However, plants growing in neighboring areas had the same or similar matK gene sequences as usual, due to the maternal inheritance of the matK gene.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR-RFLP approach to study organellar genome diversity has been reported in many plants (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011). This work aimed at deciphering the polymorphism in the chloroplast and mitochondrial genomes in the Saccharum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Specific chloroplast genes and/or intergenic spacers can be amplified (Taberlet et al, 1991;Demesure et al, 1995;Tsumura et al, 1995Tsumura et al, , 1996Dhingra and Folta, 2005;Heinze, 2007). The amplicons can be directly sequenced or restriction endonuclease digested (PCR-RFLP) or subjected to cleaved amplified polymorphic sequence (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%